A New Hypothesis of the Origin of Life ─ Did eukaryotes evolve from the "tamago of life"? - Asano, Katsura (My University, 2021)
This article is an English translation of the following original article written in the Japanese language and published in 2008. Its English translation was completed and posted by the same author in March, 2021. Life on Earth is generally classified into bacteria, archaea, and eukaryotes, but how eukaryotes, including humans, were originated is a mystery. Recent achievements in geobiochemistry and genomic biology have overturned previous thoughts that the eukaryotes are relatively new and instead showed that their origin can be as old as those of bacteria and archaea. Therefore, searching for the origin of eukaryotes must be reconciled with searching for the origin of cells, and a certain scenario emerges when this problem is considered along with Earth’s geological history.